Aircraft turbine engine monitoring experience : an overview and lessons learned from selected case studies - Birkler, J. L., 1944-; Nelson, J. R.; Rand eBooks (Santa Monica, CA : RAND, 1980)
Two approaches have evolved in attempts to improve engine operations, maintenance, and management while reducing support costs. The first concentrates on short-term practices (inflight data are recorded in a snapshot mode). The second approach focuses on long-term benefits through improved knowledge of the operating environment (data must be recorded continuously on at least a few aircraft). Engine duty-cycle research by the military services has demonstrated that neither the services nor the manufacturers have a clear idea of power requirements and frequent throttle movements during operational sorties in fighter aircraft and have generally overestimated engine parts life and underestimated expected life-cycle costs. The narrow concept of cost savings over the short term should not be the sole criterion on which monitoring systems are judged. Monitoring systems for recent and future engines should include continuously recorded data now that reliability, durability, and cost issues are almost on an equal footing with performance.
"August 1980."
This research was conducted under RAND's Project Air Force.
Includes bibliographical references (p. 91-97).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Airplanes -- Turbojet engines -- In-flight monitoring; Airplanes, Military -- Testing; Electronic books